2012
DOI: 10.1039/c2nr31832f
|View full text |Cite
|
Sign up to set email alerts
|

Salt-mediated kinetics of the self-assembly of gold nanorods end-tethered with polymer ligands

Abstract: Studies on the self-assembly of metal nanoparticles (NPs) in the presence of ions are motivated by the biosensing applications of NP clusters and the capability to control the morphology of clusters of oppositely charged NPs. The effect of ions has been explored for the self-assembly of metal NPs capped solely with ionic ligands, whereas, in general, the surface of NPs can be coated with a mixture of ligands interacting with each other by non-electrostatic forces. In the present work, we examined the kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…143 Lastly, the authors reported that in the presence of salts, the major driving force for selfassembly is a decrease in solubility of the PS ligands rather than a screening of the electrostatic repulsion. 144 Photo-crosslinking of poly(styrene-co-isoprene) end-functionalized gold nanorods was also demonstrated as a useful means to covalently fix the bond angles in the chains. 145 This journal is © The Royal Society of Chemistry 20xx d) random copolymers and e) block-copolymers from nanorods of two different lengths, and f) random copolymers from gold and palladium nanorods.…”
Section: From Polymer-tethered Metal Nanorodsmentioning
confidence: 99%
“…143 Lastly, the authors reported that in the presence of salts, the major driving force for selfassembly is a decrease in solubility of the PS ligands rather than a screening of the electrostatic repulsion. 144 Photo-crosslinking of poly(styrene-co-isoprene) end-functionalized gold nanorods was also demonstrated as a useful means to covalently fix the bond angles in the chains. 145 This journal is © The Royal Society of Chemistry 20xx d) random copolymers and e) block-copolymers from nanorods of two different lengths, and f) random copolymers from gold and palladium nanorods.…”
Section: From Polymer-tethered Metal Nanorodsmentioning
confidence: 99%
“…Nano Res. Kumacheva and co-workers enhanced the patchiness of the CTAB-coated gold nanorods by the functionalization of their tips with thiol-terminated polystyrene (PS) chains, which enabled the formation of linear and cyclic colloidal polymers when dispersed in binary solvent mixtures [22][23][24][25][26][27]. The driving force of the polymerization of the tip-functionalized nanorods derived from the solvation free energy reduction between the isolated particles and their assembly.…”
Section: Introductionmentioning
confidence: 99%
“…To validate the argument about competing E h and E el , we conducted NP self-assembly in the DMF/water mixture in the presence of NaCl. The addition of NaCl to the DMF/water mixture reduced the quality of solvent for the PS ligands 23 and suppressed the electric double layer interactions of the NPs, 24 thus favoring “non-directional” hydrophobic forces and the formation of globules. This trend is shown in Table 1: with increasing content of NaCl in the DMF/water mixture, C → G transitions took place, with an intermediate regime, in which both species were present.…”
mentioning
confidence: 99%